The Problem of Transferring New Concepts of Prospective Studies and Globalization into Arabic - Abdul Hay, Authoul Walid Salim (Dirasat: Human and Social Sciences, 2024)
Objectives: This study involves a terminological study of two political fields. The first field focuses on prospective studies in political science and the evolution of its political thought (methodology and content). The second field pertains to Globalization and explores its representation in Arabic from a methodological and objective point of view, with a particular emphasis on the defining concepts of its political, social, and economic impact. Methods: The research methodology adopted for the study employs a conceptual analysis of English concepts. Twenty-five problematic concepts are specified, and from these, the most frequently occurring Arabic equivalents within our corpus are identified. The onomasiology terminological approaches (Aito and Igwe, 2011) used by Arabic researchers, such as conversion, lexical creativity, and borrowing, are then analyzed. Results: The study reveals that the concepts of prospective studies and Globalization are primarily of a technical nature, necessitating a technical knowledge system. The lack of this technical background in the Arabic knowledge system makes it challenging to accurately capture the exact meaning of a new term and translate it into Arabic. We propose the Arabic equivalent that most closely encompasses the original meaning and concept for these 25 problematic concepts. Conclusions: This study concludes that the difficulty in translating these concepts and methodological techniques of the two fields lies not so much in the Arabic language itself, but rather in the Arabic cognitive system. This system's limitations stem from a lack of information, an underdeveloped scope of thought, and an adherence to a value system incongruous with the significant changes that have blurred temporal and spatial boundaries in some respects.